Olivia’s Kingdoms: Corresponding with Carby’s Imperial Intimacies in The Woman of Colour - Jarvis, J. (Romanticism on the Net, 2024)
This essay takes up and practices related methodologies from Hazel Carby’s Imperial Intimacies: correspondence and “always progressing backwards.” The essay posits that Imperial Intimacies and The Woman of Colour correspond across time, both as works about the enfleshment of “imperial intimacies” and as formal articulations of Black being in/through contradiction. Anachronisms in the novel demonstrate the contingency of historical understanding that allows The Woman of Colour to be read necessarily as both an imperial and anti-imperial work. Correspondence in both works to invert Hegel’s configuration of self-other, thereby creating the possibility for unfixed intersubjectivity. Reading The Woman of Colour with Carby (ac)knowledges Olivia Fairchild’s taxonomic shifting from human to animal to plant and back not only as reiterating the Linnean/Enlightenment threshold of Black life’s creation/destruction but also, following Zakiyyah Iman Jackson, a rupture of humanist unity through/to the mutability of Black being.